2005
DOI: 10.1097/01.ju.0000154354.06892.ba
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Calmette-Guerin Tokyo172 Substrain for Superficial Bladder Cancer: Characterization and Antitumor Effect

Abstract: High viability, good dispersion and efficient binding to tumor cells by BCG bacilli in the Tokyo172 preparation seem to be the main reasons for the lower clinical dose of this preparation compared with the Connaught preparation (18 vs 81 mg dry weight).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…Fourth, one confounding issue that could have a clinical impact on all presented studies including ours is the fact that the number of colony-forming units is different in various strains [23]. However, in the study conducted by Inamoto et al [24] comparing low-dose Tokyo 172 strain and regular dose Connaught strain, it was shown that low-dose Tokyo 172 strain caused less adverse events, although the difference was not significant.…”
Section: Limitations and Strengthsmentioning
confidence: 59%
“…Fourth, one confounding issue that could have a clinical impact on all presented studies including ours is the fact that the number of colony-forming units is different in various strains [23]. However, in the study conducted by Inamoto et al [24] comparing low-dose Tokyo 172 strain and regular dose Connaught strain, it was shown that low-dose Tokyo 172 strain caused less adverse events, although the difference was not significant.…”
Section: Limitations and Strengthsmentioning
confidence: 59%
“…Two year recurrence free survival rates weren't significantly different: 73.2% and 68.8%, respectively. These two strains have also been compared in a mouse model [9]. Tumor cells with various doses of both BCG strains were injected in the flank of syngenic mice.Tokyo172 achieved similar tumor suppression at a lower dose than Connaught.…”
Section: Discussionmentioning
confidence: 99%
“…50 Theoretically a BCG preparation with high viability, good dispersion and smaller bacillus size might be better able to enter the systemic circulation to cause serious infection. The doses stated on the BCG product labels are approximately the same (80 mg for the Tokyo 172 strain and 81 mg for the Connaught strain), but the Connaught strain is provided in powder form, whereas the Tokyo 172 strain has 70% moisture content.…”
Section: Different Clinical Outcomes Afforded By Bcg Strainsmentioning
confidence: 99%